High Temperature Treatment of Diamond Particles Toward Enhancement of Their Quantum Properties - Torelli, Marco D.; Nunn, Nicholas A.; Jones, Zachary R.; Vedelaar, Thea; Padamati, Sandeep Kumar; Schirhagl, Romana; Hamers, Robert J.; Shames, Alexander I.; Danilov, Evgeny O.; Zaitsev, Alexander; Shenderova, Olga A. (Frontiers in Physics, 2020)
Fluorescence of the negatively charged nitrogen-vacancy (NV-) center of diamond is sensitive to external electromagnetic fields, lattice strain, and temperature due to the unique triplet configuration of its spin states. Their use in particulate diamond allows for the possibility of localized sensing and magnetic contrast based differential imaging in complex environments with high fluorescent background. However, current methods of NV- production in diamond particles are accompanied by formation of a large number of parasitic defects and lattice distortions resulting in deterioration of the NV- performance. Therefore, there are significant efforts to improve the quantum properties of diamond particles to advance the field. Recently it was shown that the rapid thermal annealing (RTA) at temperatures much exceeding the standard temperatures used for NV- production can efficiently eliminate parasitic paramagnetic impurities and, as a result, by an order of magnitude improve the degree of hyperpolarization of 13C via polarization transfer from optically polarized NV- centers in micron-sized particles. Here, we demonstrate that RTA also improves the maximum achievable magnetic modulation of NV- fluorescence in micron-sized diamond by about 4x over conventionally produced diamond particles endowed with NV-. This advancement can continue to bridge the pathway toward developing nano-sized diamond with improved qualities for quantum sensing and imaging.